Liceu Cuiabano-MT : a arquitetura enquanto elemento curricular (1937-1944) - Castro, Thalita Pavani Vargas de (2023)
This thesis is the result of doctoral research developed in the Graduate Program in Education at the Federal University of Mato Grosso. Its object of study is the school architecture of Colégio Liceu Cuiabano (1937-1944), one of the first educational institutions of secondary education in the state, created in the 19th century in Cuiabá - MT. Its purpose was to prepare, above all, the children of part of the local elite for the admission process to higher education. Given the historical context of its creation and installation, which spans more than 140 years of operation, this research aims to understand how the process of planning the school architecture of Liceu Cuiabano was developed until the construction and use of the building. The time frame covers the 1930s and 1940s, precisely the period in which Cuiabá underwent transformations that effects substantially altered the daily life of the capital, with the execution of the “offical building jobs” program that resulted in the construction of the Liceu Cuiabano, inaugurated in 1944. Therefore, the research is articulated from the following starting question: how was the school architecture of Liceu Cuiabano conceived and built considering its purpose? In order to answer this question, the defined methodological procedures are based on the historical approach, carried out through a historiographical operation (CERTEAU, 2002) that begins with the process of locating the sources, duly gathered, selected and catalogued, so that later the process of the writing and analysis was articulated both to the research object and to the context in which the institution was inserted. The survey of documentary sources was carried out in the Public Archive of the State of Mato Grosso (hereby APMT), in the collections of the Research Group History of Education and Memory (hereby GEM/UFMT) and in the online collection of the National Library's Hemeroteca Digital. This documentation is composed of messages, minutes, decrees, legislation, student newspapers and non-specialized newspapers of wide circulation aimed at the general public and which deal with the context and political organization of Mato Grosso, secondary education and Liceu Cuiabano among the decades from 1930 to 1940. The analyzes were based on the theoretical-methodological framework, guided by the central concepts proposed for this study, that is: educational institution (MAGALHÃES, 2004); school architecture (ESCOLANO, 2001); and representations and appropriations (CHARTIER, 2011). So, the partial results indicate that school architecture, as a curricular element, taught and formed the subjects who were part of Liceu Cuiabano's daily life through the organization and pedagogical use of this space in the training of students. Therefore, the architectural construction of Liceu Cuiabano consolidated an ideal urbanism project, made up of human actions, in order to dictate, teach, educate and form the citizen of the time within a process imbued with behaviors, feelings, values and knowledge.